2015
DOI: 10.4102/pythagoras.v36i1.281
|View full text |Cite
|
Sign up to set email alerts
|

Teacher narratives in making sense of the statistical mean algorithm

Abstract: Teaching statistics meaningfully at school level requires that mathematics teachers conduct classroom discussions in ways that give statistical meaning to mathematical concepts and enable learners to develop integrated statistical thinking. Key to statistical discourse are narratives about variation within and between distributions of measurements and comparison of varying measurements to a central anchoring value. Teachers who understand the concepts and tools of statistics in an isolated and processual way c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In this connection, commognitive as a lens in reasoning research has been carried out by previous researchers, such as research on mathematical reasoning (Jeannotte & Kieran, 2017;Rabin et al, 2013), geometric reasoning (Toscano et al, 2019;Wang, 2016;Wang & Kinzel, 2014), and statistical reasoning (Lampen, 2015;Park & Lee, 2014;Rahmatina et al,2020). This shows that commognitive reasoning has become a trend in reasoning research.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this connection, commognitive as a lens in reasoning research has been carried out by previous researchers, such as research on mathematical reasoning (Jeannotte & Kieran, 2017;Rabin et al, 2013), geometric reasoning (Toscano et al, 2019;Wang, 2016;Wang & Kinzel, 2014), and statistical reasoning (Lampen, 2015;Park & Lee, 2014;Rahmatina et al,2020). This shows that commognitive reasoning has become a trend in reasoning research.…”
Section: Introductionmentioning
confidence: 84%
“…However, not many researchers have studied how the commognitive framework has been used as a tool in the statistical reasoning process. Lampen (2015) and Park & Lee (2014) investigate the use of commognitive framework in statistical reasoning. Lampen's research (2015) focused on analysing Sfard's commognitive theory (2008) on teachers' narrative in making sense of the average algorithm as a discourse basis of variability measure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors develop analytical language to examine how coherently a teacher moves from a stated mathematical problem towards a solution. Lampen (2015) uses the concept of MDI to explore required teacher knowledge and skill to meaningfully conduct classroom discussions on the statistical mean algorithm in a connected manner. Contrastingly, Berger (2013) examines student discourse from the perspective of Sfard's theory of commognition.…”
Section: Discourse and Speakingmentioning
confidence: 99%
“…The form of the narrative was indicated when the students explained the theorem of a rectangular area using the concepts of addition and subtraction. Similarly, Lampen (2015) studied the narrative of the concept of statistics in a teacher. He found that initially, the teacher could not create narratives about the mean as a statistical object.…”
Section: Introductionmentioning
confidence: 99%